Urinary Cortisol, Aggression, Dominance and Competition in Wild, West African Male Chimpanzees - Preis, Anna; Samuni, Liran; Deschner, Tobias; Crockford, Catherine; Wittig, Roman M. (Frontiers in Ecology and Evolution, 2019)
High dominance status is associated with fitness benefits in many social mammals. Yet, attaining and maintaining a high social status often comes with elevated energetic costs. Dominance rank-related exposure to energetic and psychosocial stressors is predicted to vary depending on the type of breeding system, the means a high rank is acquired and maintained, and the stability of the dominance hierarchy. Using behavioral data and urinary cortisol levels, we investigated whether a high dominance rank is associated with elevated energetic costs in Taï male chimpanzees and whether the relationship between male dominance rank and cortisol levels varies between stable and unstable dominance periods. Additionally, we investigated potential sources of energetic and psychosocial stress linked to competition over dominance status and mating opportunities. We found that higher-ranking males gave more aggressions than lower ranking males in stable and unstable dominance periods, but that dominance rank and urinary cortisol levels were not associated in either period. Urinary cortisol levels were higher in all males in unstable compared to stable dominance periods, whereas aggression rates showed the reversed pattern, with higher rates in stable periods. Our results indicate that dominance maintenance is not associated with elevated physiological stress for dominant Taï male chimpanzees, and that social instability exposed all males to psychosocial stress, despite lower rates of aggressive interactions. Overall, these findings suggest that male chimpanzees adjust competitive behavior to context dependent conditions, possibly by means of predictability of outcomes of social interactions, and use conflict management strategies, such as avoidance of aggression potentially diminishing the risk of escalation.